International Relations : Theories in Action - Zimmermann, Hubert (SAGE Publications, Ltd. (UK), 2024)
The definitive applied theory textbook that helps you make sense of global issues through theoretical concepts. Not presupposing any prior knowledge, this introduction equips you with the skills to use theories as adaptable tools to tackle complex global issues. Adopting a critical and questioning approach, you will be equipped in theory as a series of tools to be used, adapted, combined, and applied when grappling with some of the most contested issues in global politics. Theoretical perspectives are brought alive as a vital tool to understand concrete historical and contemporary examples. This indispensable text starts by examining key theories spanning constructivism and postcolonialism to realism and liberalism with a real-world perspective which prioritises empirical purchase. From here, chapters take a critical, questioning approach to tackle core problems of international politics – from armed conflict and financial markets to the climate crisis, global inequality, gender and race. This text is the ideal companion for all undergraduate and postgraduate students of global affairs. Hubert Zimmermann is Professor of International Relations at Philipps University of Marburg, Germany. Milena Elsinger is Head of the student information department at Philipps University of Marburg, Germany. Alex Burkhardt teaches at the Bundessprachenamt in Koblenz, Germany and previously taught at Philipps University Marburg, Germany.